Pengaruh Pemberian Five Fingers Hypnosis Therapy Dalam Menurunkan Tingkat Kecemasan Masyarakat Paska Bencana Banjir - Subhan nur Rahman; Anita Herawati (Institut Citra Internasional, 2023)
Banjarmasin is one of the provinces with flood emergency response status, precisely in Paku Alam Village, Sungai Tabuk District, Banjar Regency. The impact felt not only causes physical problems, but causes serious psychological problems. The purpose of this study was to find out the impact of giving Five Fingers Hypnosis Therapy in reducing the level of community anxiety after the flood disaster in Paku Alam Village, Banjar Regency. The research method used was pre-experimental with a one group pretest-posttest design, the sampling location was in Paku Alam Village, East Banjarmasin District. The sample in this study amounted to 30 people. The results of the study showed that giving five finger hypnosis therapy was proven to be able to overcome and reduce the level of community anxiety after the flood disaster in Paku Alam Village, Banjar Regency. It is hoped that survivors can apply Five Fingers Hypnosis Therapy independently in order to minimize the risk of serious mental health problems.